NANOTEHNOLOGY AND WONDERFUL WORLD OF METAMATERIALS - Anatolie SIDORENKO (Academy of Sciences of Moldova, 2014)
In Institute of Electronic Engineering and Nanotechnologies of Moldavian Academy of Sciences is developing a novel research direction – technologies of nanostructures and metamaterials preparation and investigation of their unusual properties. Why such materials attract a rising interest all over the world? What is the main reason to take part in this „racing on the atomic scale”? The article highlights the history of discovery and some of main peculiarities of the metamaterials, making them very promising for technical applications.